Biomimicry in the Context of Stabilised Porous Clays - Arya Assadi-Langroudi (Biomimetics)
This study explores the etymological roots of nature and nature-inspired design within the context of soil stabilisation. It outlines Aristotle’s doctrine of hylomorphism and applies these concepts to develop a pathway for the stabilisation of clays within their original porous or looser structure through interparticle modifications. A biopolymer is introduced to a base clay thorough a procedure that imitates forms, matter, generative processes, and functions of arbuscular mycorrhizal (AM) fungi. For the first time, the void ratio was progressively increased from 0.50 to 0.70, and the air ratio from 0.15 to 0.33, reflecting a systematic transition from a denser to a looser packing state. A 20% increase in shear wave velocity indicated enhanced interparticle engagement following treatment. This reinforcement effect contributed to the preservation of stiffness and residual strength, despite a 120% increase in air ratio and a 63% reduction in degree of saturation, alongside a modest improvement in unconfined compressive strength. The findings presented here mark a departure from both conventional and emerging stabilisation techniques, enabling engineered soil to remain porous, to loosen with time, and to continue delivering engineering and ecological services.